Study on molecular dynamics of the effect of defects on the friction properties of single crystal metals. (4th July 2019) - Zongtao, Chen; Wei, Xiong; Gang, Xu; Yumei, Li; Huaping, Mei; Tao, Ding; Shufen, Xiao
Abstract: In order to study the effect of vacancy defects in different directions and concentrations on the friction force of single crystal iron, Using the process of sliding friction monocrystalline iron matrix with diamond hemispheric probe as the research object, a molecular dynamics model was established and simulated. The results of the study indicate that：The interface barrier potential at the defect of single crystal iron increases the average friction force at the defect, and the friction force of single crystal iron at the defect is greater than that of perfect single crystal iron；The average friction force of single crystal iron increases with the increase of defect concentration; The above research results enrich the theory of friction and wear between the surfaces of the micronanoscale components and provide sufficient theoretical basis and guidance for the design and development of micronanoscale devices.